A triboelectric and pyroelectric hybrid energy harvester for recovering energy from low-grade waste fluids - Jiang, Dongyue; Su, Yunpeng; Wang, Kun; Wang, Yutao; Xu, Minyi; Dong, Ming; Chen, Guijun (Nano energy, 2020)
Low-grade waste energy is widely available in industrial processes, and it typically appears in the form of thermal fluids. Types of technologies are developed for harvesting the thermal energy from these fluids. However, the thermal fluid not only possesses thermal energy, but also contains a large amount of kinetic energy. In this study, a hybrid device is proposed for harvesting both the thermal and kinetic energy of the thermal fluids. A free-standing type triboelectric nanogenerator (TENG) is employed for harvesting the kinetic energy, while a pyroelectric generator (PENG) is used for harvesting the thermal energy. Output performance of discrete water droplets with temperature of 5 °C, 25 °C, 45 °C and 65 °C are compared in both the TENG and PENG devices. The effects of the device inclination angle, and droplet released height are discussed. The analyses are conducted based on high-speed video recording of the droplet dynamics on the device as well as numerical simulation. The results indicate the droplet temperature, device inclination angle and droplet released height affect the droplet dynamics significantly. Further, the variation of droplet dynamics greatly affects the output performance of both the TENG and PENG. The peak output power of the TENG decreases with the increase of droplet temperature, while the output power of the PENG increases with the temperature variation. A hybrid energy harvester was fabricated and a peak power density of 2.6 μW/cm2 was achieved. A maximum energy increment of 238% was obtained by the hybrid harvester, as compared to the pure PENG device. The harvested energy was able to light up 28 commercial LED light bulbs. A TENG and PENG hybrid energy harvester for kinetic and thermal energy harvesting from hot fluids. [Display omitted] •A triboelectric/pyroelectric hybrid energy harvester is proposed.•The hybrid harvester produces 238% output energy than pure PENG.•The proposed hybrid harvester could light up 28 commercial LED bulbs.